Pós-graduação em relações internacionais no Brasil: Anotações sobre sua institucionalização - Vigevani, Tullo [UNESP]; Thomaz, Laís Forti; Leite, Lucas Amaral Batista (FapUNIFESP (SciELO), 2016)
In this article, the authors seek to discuss the state-of-the-art of the academic production on International Relations in Brazil, with focus on the graduate level. The premises guiding the study are: a) there has been production of thought, research, and teaching before the institutionalization of the area in the 1980's; b) from the 2000's onwards, the area has been consolidated. The article is divided into five sections, including the introduction and conclusions. The second section presents the first thinkers and researchers in the field of international relations in Brazil. The third approaches the institutionalization from the perspective of the quantitative growth of ungraduated courses, graduate programs and researches. The fourth section analyzes, through quantitative and qualitative data, how the consolidation of graduate studies work, indicating issues worthy of further consideration such as the impact and the autonomy of the area.
Graduate studies on international relations in Brazil: Notes on their institutionalization
Keywords: Brazil; Graduate studies; Institutionalization; Intellectual production; International relations